Four Azadirone-Type Limonoids from Chisocheton Pentandrus Stem Bark and Their Cytotoxic Acitivity Against Mcf-7 Breast Cancer Cell Lines - Supratman, Unang; Runadi, Dudi; Naini, Al Arofatus; Purnama, Purnama; Mayanti, Tri; Harneti, Desi; Nurlelasari, Nurlelasari; Maharani, Rani; Farabi, Kindi; Nafiah, Mohamad Azlan (Molekul, 2024)
ABSTRACT. Limonoid group belongs to triterpenoid that has undergone further oxidation accompanied by the loss of four carbon atoms to form a furan ring in the chain. This limonoid compound is often found in the Chisocheton genus. Limonoid compounds have been known as compounds with high structural variations and this makes limonoids have diverse and interesting activities, including cytotoxic and anticancer. In the course of our continuing study for limonoid constituents that have cytotoxic activity against cancer cell lines, methanol extract of stem bark from the Chisocheton pentandrus plant provides significant activity. The methanol extract was separated using various chromatographic techniques in the normal and reverse stationary phase to produce four azadirone-type limonoid compounds (1-4). The elucidation structure of 1-4 was determined using spectroscopic methods including, UV-Visible, IR, and 1D-NMR as well as optical rotation. All four known compounds were established as trichilenone acetate (1), toonaciliaton C (2), 11α-acetoxiazadiron (3), and 16β-hydroxydisobinine (4). The cytotoxicity of compounds 1-4 was assessed by examination using the resazurin method, which showed that compound 4 was the promising constituent against the MCF-7 cells with an IC50 value of 43.1 µM and was stronger than its positive control. Keywords: Azadirone-type limonoid, Chisocheton pentandrus, cytotoxic activity, Meliaceae.